1996
DOI: 10.1007/bf03162245
|View full text |Cite
|
Sign up to set email alerts
|

EPR studies of technetium complexes in frozen solution

Abstract: Analysis of the EPR spectra of Te complexes in frozen solution has given information about the behaviour of these complexes not readily obtainable by other means. In particular, spectral sirnulations have enabled the determination of the quadrupole interaction parameter, Q, and thus to the evaluation of subtle electronic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
(37 reference statements)
2
7
0
Order By: Relevance
“…This view shows that a very broad spectrum, most likely from a spin > 1/2 species, becomes evident at low temperatures, while the spin = 1/2 species centered at g ~ 2, shown in Figure 5.10, is only faintly visible. Baldas et al (1996) reported a similar spectrum for [Bu 4 N] 2 [Tc(IV)Cl 6 ], also in methylene chloride, at 5.7 K.…”
Section: Development Of 99 Tc Epr Characterization Techniquementioning
confidence: 72%
See 2 more Smart Citations
“…This view shows that a very broad spectrum, most likely from a spin > 1/2 species, becomes evident at low temperatures, while the spin = 1/2 species centered at g ~ 2, shown in Figure 5.10, is only faintly visible. Baldas et al (1996) reported a similar spectrum for [Bu 4 N] 2 [Tc(IV)Cl 6 ], also in methylene chloride, at 5.7 K.…”
Section: Development Of 99 Tc Epr Characterization Techniquementioning
confidence: 72%
“…But the possibility remains that the triplet state of Tc(V) [TcOCl 5 ] 2might exist; if so, it should generate its own EPR response. Additionally, the pertechnetate reduction in concentrated HCl does not stop when Tc(V) is formed, it proceeds further to the thermodynamically stable [TcCl 6 ] 2-, which has an EPR-active Tc(IV) center (Baldas et al 1996). So this complex system is especially suited to develop the EPR method for Tc characterization and to understand Tc fundamental chemistry.…”
Section: Development Of 99 Tc Epr Characterization Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Linewidth considerations limit the component of the superhyperfine interaction parallel to the Tc≡N direction to less than 2 × 10 –4 cm –1 . In contrast to this, the EPR spectrum of the analogous [ReNF 4 ] – shows resolved hyperfine couplings of 19 F in the parallel part (quintets with the intensity ratio of 1:4:6:4:1) as well as in the perpendicular part (distorted triplets) …”
Section: Resultsmentioning
confidence: 89%
“…More promising were reactions of “nitridotechnetic(VI) acid”, a black‐brown, polymeric solid of the tentative composition {TcN(OH) 3 } n , which is formed from hydrolysis of Cs 2 [TcN X 5 ] ( X = Cl, Br) salts, and readily dissolves in aqueous hydrofluoric acid. The resulting solutions contain only one paramagnetic species, [TcNF 4 ] – , which gives an intense axially‐symmetric EPR spectrum with well‐resolved ten‐line patterns in the parallel and perpendicular parts (Figure ).…”
Section: Resultsmentioning
confidence: 99%